"Wherever I Go, I Have It Inside of Me": Indigenous Cultural Dance Narratives as Substance Abuse and HIV Prevention in an Urban Danza Mexica Community - Angela R. Fernandez; Ramona E. Beltrán (Frontiers Media S.A., 2022)
Introduction"Mexican American Indian" (MAI) is a large and diverse population for which little empirical research on alcohol and other drug (AOD) use and HIV is available, yet for which there is a disproportionate risk. Indigenous health narratives and participation in place- and settings-based cultural practices can be protective in chronic and co-occurring disease prevention and health promotion for Indigenous people. This study explores the role of participation in cultural dance in generating narratives of prevention and health promotion among a sample of MAIs from an Urban Danza Mexica Community (UDMC), framed within a decolonizing narratives of health (DNOH) model.MethodsThis secondary data analysis (n = 9) is drawn from a qualitative AOD and HIV health needs assessment of UDMC living in the Pacific Northwest and the Rocky Mountain West (n = 21). This study uses a community-based participatory research approach and employs narrative, Indigenized methods to analyze in-depth interviews from adult cisgender females (n = 5) and males (n = 4). The DNOH model is developed as a relational, analytic framework that contextualizes Indigenous stories in relationship to three distinct yet interconnected levels-the personal, the communal, and Indigeneity in the larger world. These levels of narrative analysis function as culturally grounded, relational pathways through which to articulate health education and promotion approaches.ResultsNarratives delve into the complex and nuanced relationships within participants' internal worlds (personal), between themselves and their Danza community (communal), and between themselves and their complex, intersectional Indigenous identities within society (Indigeneity). Stories of ancestral teachings about health and prevention shared within the Danza circle create spaces wherein participants navigate complex conversations that resist oppressive colonial narratives, reconnect with and strengthen their Indigenous identities, and strive toward ancestral visions of health and well-being.DiscussionThis study contributes to Indigenized theoretical and methodological expansion and the development of place/settings-based, narrative, cultural health interventions aimed at preventing chronic and co-occurring disease and promoting wellness among populations similar to the UDMC. Identifying cultural practices as Native Hubs (relational, socially constructed places) that foster decolonizing narratives helps increase understanding of their role in public health education and promotion through recognition of Indigenous knowledge systems and frameworks.